Curriculum according to knowledge economy skills (Journal of the College of Basic Education, 2023)
The research aims to:A curriculum based on knowledge economy skills.The researcher recommended a number of recommendations, including:The use of the proposed curriculum contributes to increasing the effectiveness of the teaching process, and increases the activity of students in the College of Basic Education and makes them the focus of the teaching process.The proposed curriculum based on the knowledge economy has an effective impact on increasing students' achievement in the Arabic language subject. The researcher suggested conducting a number of studies, to complement this research, including:Conducting a study similar to the current research on academic stages.Conducting a similar study to identify the impact of the curriculum on other branches of the Arabic language, such as rhetoric and expressionBuilding the Arabic language curriculum in the faculties of education for departments other than specialization, according to the current researchMethod.